An experience of vocabulary teaching in an english immersion class in a public school in Bogotá (2019)
The action research is a model that allows teachers to improve their educational practice from a critical reflection. After making observations in the seventh and ninth grades of the Enrique Olaya Herrera school in the immersion classroom, it was evident that the students had a limited vocabulary that restricted them to express what they wanted to say. For this reason, during four months the research emphasized in three aspects: increasing vocabulary, teach the intelligible pronunciation of the new words acquired, and, finally, promote the participation of students in the immersion classroom. To accomplish these objectives, the communicative and audiolingual methods were used. In addition, guides, songs, and flashcards were used to help students acquire new vocabulary. As a conclusion to this research, the data collected from the quizzes, questionnaires, the interview, and my own observations evidence advancement in students¿ learning of vocabulary.